Transgression of WCAG 2.0 Constraint in Indian Government Websites - Koujalagi, Ashok (International Journal of Computer Sciences and Engineering, 2025)
Sites of Indian Government fills in as a medium of transmission of Information. Along these lines, the sites of government organizations ought to be available to all. Since, an ordinary individual can get to the sites effortlessly however a man with incapacity (PwD) who might be outwardly disabled couldn't get to the sites effectively. This is the way Web availability came into picture. Ordinariness of WCAG 2.0 rules by site pages is a noteworthy factor in estimating the availability of sites all around. The principle point of this investigation is to decide if the general population with inabilities can access and utilize State Government sites in India effortlessly or not. By utilizing web availability assessment instrument namely Power Mapped Sort Site, we have assessed 10 sites of Indian Government and gave the after effects of examination in this paper. Likewise, we came to a resolution where dominant part of the sites doesn’t meet the necessities WCAG 2.0. In this paper we have recognized and examined the most damaged WCAG. Our exploration may bring issues to light to the web engineer about these encroachments and urge them to manufacture sites that can wind up available to all